2021
DOI: 10.21037/atm-21-4386
|View full text |Cite|
|
Sign up to set email alerts
|

Atractylodin may induce ferroptosis of human hepatocellular carcinoma cells

Abstract: Background: It has been reported that atractylodin has a potential antitumor effect. This study aimed to investigate the effects of atractylodin on Huh7 and Hccm hepatocellular carcinoma (HCC) cells and its molecular mechanism.Methods: Huh7 and Hccm cells were cultured in vitro, and their viability was detected by CCK-8 assay and the half inhibitory concentration (IC50) was calculated. The cells were treated with different concentrations of atractylodin, and the migration and invasion ability of cells was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…As the main subunit of ferritin, FTL directly affects iron homeostasis ( Arber et al, 2016 ). Current studies have found that FTL may be regulated by the DNA damage response of serine/threonine kinase ATM, hypoxia, atractylodin, and other factors, resulting in ferroptosis ( Liu et al, 2020b ; Chen et al, 2020 ; He et al, 2021 ). FTL may also be involved in the development of tumors, such as the proliferation rate of HeLa cells and glioblastoma multiforme (GBM) cells ( Wu et al, 2016 ) and the drug resistance process of breast cancer ( Cozzi et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main subunit of ferritin, FTL directly affects iron homeostasis ( Arber et al, 2016 ). Current studies have found that FTL may be regulated by the DNA damage response of serine/threonine kinase ATM, hypoxia, atractylodin, and other factors, resulting in ferroptosis ( Liu et al, 2020b ; Chen et al, 2020 ; He et al, 2021 ). FTL may also be involved in the development of tumors, such as the proliferation rate of HeLa cells and glioblastoma multiforme (GBM) cells ( Wu et al, 2016 ) and the drug resistance process of breast cancer ( Cozzi et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Circulating transcription of FTL is significantly upregulated in samples from HCC patients and maybe a new target for the diagnosis and treatment of HCC ( Wang et al, 2009 ; Sayeed et al, 2020 ). The decrease in FTL protein is associated with ferroptosis in HCC cells ( He et al, 2021 ), but its role and mechanism remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…59 In HCC cells, atractylodin was observed to induce the accumulation of lipid peroxides and ferroptosis by inhibiting GPX4 expression, leading to the suppression of HCC progression. 64 Therefore, it is suggested that ferroptosis plays a significant role in the inhibitory effect of atractylodin on HCC cells.…”
Section: Induction Of Ferroptosismentioning
confidence: 99%
“…It also promotes iron peroxidation and lipid ROS metabolism to induce ferroptosis in HCC cells ( Li Y et al, 2022 ). Atractylodin decreases GPX4 and FTL protein expression, upregulates ACSL4 and TFR1 protein expression, and increases ROS levels in liver cancer cells ( He et al, 2021 ). In recent years, several studies have reported that active components of Artemisia annua can induce ferroptosis and inhibit HCC.…”
Section: Current Stage Of Pharmacological Study Of Ferroptosis In Hep...mentioning
confidence: 99%